2019
DOI: 10.2147/ott.s208924
|View full text |Cite
|
Sign up to set email alerts
|

<p>Oridonin overcomes the gemcitabine resistant PANC-1/Gem cells by regulating GST pi and LRP/1 ERK/JNK signalling</p>

Abstract: Background: Chemotherapy remains a primary treatment method for advanced pancreatic cancer. However, chemotherapy resistance can influence the therapeutic effect of pancreatic cancer. The resistance mechanism of chemotherapeutic agents such as gemcitabine, which is an agent typically used to treat pancreatic cancer, is complicated and can be influenced by genes and the environment. Oridonin is a tetracyclic diterpenoid compound extracted from the traditional Chinese herb Rabdosia labtea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…30 Oridonin can overcome gemcitabine resistance in PANC1/ Gem cells by regulating GSTπ and LRP1-ERK-JNK signaling, inducing cell apoptosis. 31 Our previous results have also demonstrated that cryptotanshinone and imatinib have a cooperative role in inducing cell apoptosis, suggesting a combination therapy for the treatment of chronic myeloid leukemia patients. 32 In this study, we proved that SSD was effective in the induction of apoptosis and activation of the MKK4-JNK pathway in pancreatic cancer cells.…”
Section: Dovepressmentioning
confidence: 88%
“…30 Oridonin can overcome gemcitabine resistance in PANC1/ Gem cells by regulating GSTπ and LRP1-ERK-JNK signaling, inducing cell apoptosis. 31 Our previous results have also demonstrated that cryptotanshinone and imatinib have a cooperative role in inducing cell apoptosis, suggesting a combination therapy for the treatment of chronic myeloid leukemia patients. 32 In this study, we proved that SSD was effective in the induction of apoptosis and activation of the MKK4-JNK pathway in pancreatic cancer cells.…”
Section: Dovepressmentioning
confidence: 88%
“…The existing literature has already documented good anti-tumor effects with more than 50 kinds of TCM in the treatment of PC, like oblongifolin C, oridonin, and Wumei. [31][32][33] PHI is a phenylethanoid glycoside isolated from the Chinese medicinal Osmanthus fragrans flower, which has been proven to have various pharmacological properties, such as anti-oxidation, hypolipidemic inhibition, and inhibition of low-density lipoprotein oxidation. 34,35 However, the mechanism of PHI-mediated anti-tumor action has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments suggested that knockdown of CDKL5 and LINC00680 decreased the expression of MDR1, MRP5 and LRP1 (Fig. 4), which are known as drugresistance genes in various cancers [30][31][32][33]. The role of MDR1 and MRP7 in docetaxel resistance were demonstrated in different types of cancer [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%